KAJIAN KRIMINOLOGIS TERHADAP PELAKU TINDAK PIDANA PEMBUNUHAN BERENCANA DAN ATAU PENCURIAN DENGAN KEKERASAN DIHUBUNGKAN DENGAN PASAL 340 JO PASAL 338 JO PASAL 365 KUHPidana (STUDI KASUS PERKARA NOMOR 377 / PID. B/ 2008/ PN. CIAMIS): Array - Rachmatin Artita; Hussein Sujana; Heru Utomo; Sumari Sumari (Program Studi Hukum Program Pasca Sarjana, 2020)
The problems in this research are (1) What factors that cause the crime of premeditated murder and / or theft with violence are related to Article 340 Jo Article 338 Jo Article 365 Criminal Code (case study case Number 377 / PID. B / 2008 / PN. Ciamis) ? (2) What consequences arises from the occurrence of criminal acts of premeditated murder and or theft with violence connected to Article 340 Jo Article 338 Jo Article 365 Criminal Code (case study case Number 377 / PID. B / 2008 / PN. Ciamis)? (3) How is the application of the elements of Article 340 Jo Article 338 Jo Article 365 of the Criminal Code in the criminal act of premeditated murder and or theft with violence (case study case Number 377 / PID. B / 2008 / PN. Ciamis)? The method used in this research is analytical descriptive, with normative juridical approach, the technique of collecting data is literature, observation and interview. The results of the study inform that: (1) Factors causing criminal acts of premeditated murder and or theft with violence are related to Article 340 Jo Article 338 Jo Article 365 Criminal Code (case study case Number 377 / PID. B / 2008 / PN. Ciamis) are because the suspect felt confused after the victim claimed to be pregnant and asked to be married. and after the suspect heard the victim's words the suspect did not give a decision to immediately marry her but the suspect gave an explanation that the suspect had a family and then the suspect returned home. Then the suspect does not immediately do what the suspect has planned because he sees an impossible situation and the suspect has no reason to invite the victim to leave the house. Article 338 Jo Article 365 Criminal Code (case study case Number 377 / PID. B / 2008 / PN. Ciamis) is: (1) Death of the victim has decided the life expectancy of the victim; (2) The death of the victim leaves deep sorrow and injury to the victim's family; (3) Death of the victim results in the loss of the victim's property; and (4) Acts of perpetrators / suspects cause public unrest and antipathy. (3) The application of the elements of Article 340 Jo Article 338 Jo Article 365 of the Criminal Code in the criminal act of premeditated murder and or theft with violence (case study case Number 377 / PID. B / 2008 / PN. Ciamis), is that the defendant MISYO BIN MUSTAR has been proven and convicted of committing a criminal act of premeditated murder in this case the court has sentenced the defendant to imprisonment for 15 (fifteen) years and burdened the defendant by paying the court fee of Rp. 1000.00 (one thousand rupiah).